PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frustescens L.) PADA BERBAGAI KOMBINASI BIOCHAR DAN BIOURIN SAPI - B. P, Iswarno; Laude, Syamsuddin; Syakur, Abd. (Fakultas Pertanian, Universitas Tadulako, 2023)
The purpose of this study was to determine the effect of combining biochar and cow bio-urine on the growth and yields of cayenne pepper plants. The research was conducted between April and July 2019 in Lagarutu of Tanamodindi Village, Palu City, Central Sulawesi Province. A randomized block design was employed with 5 treatments: control with no biochar and bio-urine added (P1), 64.43 g husk charcoal /plant with no bio-urine (P2), 64.43 g husk charcoal + 40 ml bio-urine/plant (P3), 64.43 g coconut shell charcoal with no bio-urine (P4), and 64.43 g coconut shell charcoal + 40 ml bio-urine/plant. The results of the study indicated that the combination of biochar and cow bio-urine had a significant effect on plant height, number of leaves, number of productive branches, time of flower appearance, number of fruits, and fruit weight. Notably, the treatment of shell charcoal biochar combined with cow bio-urine (P5) resulted in the most favorable growth and yields for cayenne pepper plants.